Aerogels Handbook 2011
DOI: 10.1007/978-1-4419-7589-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Cellulosic and Polyurethane Aerogels

Abstract: International audienceThis chapter focuses on isocyanurate and cellulose-based aerogels. First, it presents the global sol-gel synthetic path by polycondensation. Then, it summarizes all the main results on these two families of organic aerogels. Finally, some of the recent advancements concerning their use for hybridization of silica aerogels are shortly presented. Through a brief description of the basics, together with a short overview of the main properties, this article highlights the huge potential of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…We initially investigated the effect of solvent composition on aerogel properties for different DMSO–acetone mixtures where X DMSO is the volume fraction of DMSO in the solvent mixture, both common solvents for isocyanate based aerogel synthesis . The samples prepared in solvents with X DMSO < 7.5% displayed precipitation rather than gelation, and no aerogels could be prepared.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We initially investigated the effect of solvent composition on aerogel properties for different DMSO–acetone mixtures where X DMSO is the volume fraction of DMSO in the solvent mixture, both common solvents for isocyanate based aerogel synthesis . The samples prepared in solvents with X DMSO < 7.5% displayed precipitation rather than gelation, and no aerogels could be prepared.…”
Section: Resultsmentioning
confidence: 99%
“…Most industrial aprotic solvents have lower δ H-bonding parameters (Table 1) and the requirement for a high δ H-bonding parameter imposes the use of DMSO or THF (Table 1), or an alternative solvent with high δ H-bonding , as part of the solvent blend. The observation that other studies on polyurethane aerogels also use solvent blends containing either DMSO or THF 17 may indicate that our optimum solvent systems may also be useful for related PUR or PUR−PIR formulations. However, a Hansen solubility parameter study for polyurea aerogels identified solvent systems with δ H-bonding between 3 and 5 MPa 1/2 as optimal, 22 in stark contrast to our data on the PUR−PIR system.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 96%
See 2 more Smart Citations